2015
DOI: 10.1016/j.micinf.2015.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Bacillary replication and macrophage necrosis are determinants of neutrophil recruitment in tuberculosis

Abstract: We previously determined that burst size necrosis is the chief mode of mononuclear cell death in the lungs of mice with tuberculosis. The present study explored the link between infection-induced necrosis of mononuclear phagocytes and neutrophil accumulation in the lungs of mice challenged with one of four Mycobacterium tuberculosis strains of increasing virulence (RvΔphoPR mutant, H37Ra, H37Rv and Erdman). At all time points studied, Erdman produced the highest bacterial load and the highest proportion and nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 35 publications
(47 reference statements)
2
37
0
Order By: Relevance
“…The key signals that initiate an innate response to the presence of M. tuberculosis-infected AMs in the lung are not known with certainty. In the 2-week period after low-dose aerosol infection with M. tuberculosis Erdman, the lung bacterial load increases by 0.3-0.4 log per day [16]. A reduced rate of phagocytosis, followed by slower growth of intracellular bacilli to a burst-sized load in diabetic AMs, could delay the induction of innate immunity by several days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The key signals that initiate an innate response to the presence of M. tuberculosis-infected AMs in the lung are not known with certainty. In the 2-week period after low-dose aerosol infection with M. tuberculosis Erdman, the lung bacterial load increases by 0.3-0.4 log per day [16]. A reduced rate of phagocytosis, followed by slower growth of intracellular bacilli to a burst-sized load in diabetic AMs, could delay the induction of innate immunity by several days.…”
Section: Discussionmentioning
confidence: 99%
“…Viability was no different in macrophages from normoglycemic or HG mice ( Figure 3D). We previously reported that the horizontal spread of M. tuberculosis infection from AMs to newly recruited macrophages, myeloid dendritic cells (mDCs), and neutrophils in the lung depends on intracellular bacterial replication to a threshold burden that triggers necrosis of the infected macrophage [15,16]. If M. tuberculosis grows more slowly in the AMs of diabetic hosts, this could delay immunostimulatory macrophage necrosis, transmission of bacilli to mDCs and neutrophils, and transfer of bacilli to lymph nodes for adaptive immune priming.…”
Section: Growth Of M Tuberculosis In Diabetic Macrophagesmentioning
confidence: 99%
“…Frequencies of neutrophils in the blood of exposed individuals inversely correlate with risk of TB [81], suggesting a protective role of neutrophils. In murine models, kinetics of neutrophils in the alveolar space parallels in situ cell death of resident macrophages [82] and fine-tunes subsequent inflammatory responses [74,83,84]. The extent of alveolar macrophage death and early tissue damage modulates preadaptive neutrophilic infiltration of the alveolar space [74,82].…”
Section: Early Lesions and Immune Events In Pulmonary Tbmentioning
confidence: 99%
“…In murine models, kinetics of neutrophils in the alveolar space parallels in situ cell death of resident macrophages [82] and fine-tunes subsequent inflammatory responses [74,83,84]. The extent of alveolar macrophage death and early tissue damage modulates preadaptive neutrophilic infiltration of the alveolar space [74,82]. Signaling through IFN-alpha receptor-1 (IFNAR1) promotes bacillary replication and death of alveolar macrophages [74].…”
Section: Early Lesions and Immune Events In Pulmonary Tbmentioning
confidence: 99%
See 1 more Smart Citation